Relationship of air quality indicators and synoptic scale circulation at 850 hPa over Athens during 1983-1995 - Kassomenos, P.a; Flocas, H.A.b; Skouloudis, A.N.c; Lykoudis, S.e; Asimakopoulos, V.d; Petrakis, M.e (Environmental Technology, 1998)
The daily relationship between synoptic circulation in the lower troposphere and air quality conditions is demonstrated over the Athens Metropolitan Area (AMA) for the period between 1983 and 1995. This approach utilises eight distinct synoptic categories at the isobaric level of 850 hPa and air quality indicators with respect to O3, NO2, CO, SO2 and black smoke (BS). It is demonstrated that high concentrations of photochemical pollutants and SO2 are closely related to the synoptic scale circulation while CO and BS show a weaker correlation. The most favourable synoptic pattern for the accumulation of high concentrations is the open anticyclonic circulation and for the occurrence of extreme events the closed anticyclone. NO2 and BS present the highest frequency of severe events. The seasonal analysis reveals that the bad and extreme air quality conditions due to O3 and NO2 prevail in the warm season while during the cold season CO and SO2 events prevail. The synoptic category representing a combination of high and low pressure systems, commonly associated with an intense wind flow over the Aegean Sea in the warm period, seems to favour the accumulation of photochemical pollutants, especially O3, over the AMA. The converse relationship was found for the SO2 case. During cold periods, the synoptic category characterised by ’zonal flow’ seems to favour the development of bad conditions for NO2 and particularly CO.
Keywords: air monitoring; Air pollution; Air quality; article; Athens; atmospheric transport; carbon monoxide; circulation; Greece; Nitrogen; Ozone; pollutant transport; seasonal variation; Smoke; troposphere; urban area